The Success Rate of Artificial Insemination Using Post-Thawed Spotted Buffaloes Epididymal Sperm - Y Yulnawati; H Maheshwari; M Rizal; A Boediono (Media Peternakan, 2013)
Spotted buffalo, an exotic species that exists in Tana Toraja, South Sulawesi, Indonesia, is getting extinct due to high number of slaughtered during a funeral ceremony, called Rambu Solo’, as well as special treatments that do not allow the male spotted buffaloes perform natural mating activity. According to that, the research was trying to start conservation program by collected the cauda epididymal sperm soon after slaughtered. Two egg yolk-based extenders with different buffers, tris hydroxyl amino methane (TEY20) and trisodium citrate dehydrate (CEY20), were used as comparison to evaluate the post-thawed epididymal sperm quality and fertilizing capacity in artificial insemination program. The results showed that the post-thawed progressive motility of epididymal sperm was 40% and 39.17%, while viability was 65.99% and 63.26% and membrane integrity was 65.43% and 63.03% in TEY20 and CEY20 extenders, respectively. The success rate of pregnancy was 46.67% using post-thawed epididymal sperm in TEY20 and 40% using the one in CEY20 extenders. In conclusion, tris-based and citrate-based extenders have similar ability to maintain the epididymal sperm quality and its fertilizing capacity.